Analysis of the Impact of Building Pile Foundations and Support Systems on the Deformation of Special-Shaped Deep Excavations - Wenfeng Liu; Zhen Yang; Yaohui Zhao; Guangbiao Shao; Jianyong Han; Wanpeng Li; Jie Mao; Hongxing Zhao; Junwei Xue; Zhenguo Li; Tianliang Li (Advances in Civil Engineering)
This study focuses on the impact of building pile foundations on the excavation of irregular deep excavations, aiming to reveal their stress characteristics and deformation behavior to optimize design and construction processes. Based on the deep excavation project in Yucheng, Shandong, this study employs a combination of on-site monitoring and numerical simulation to analyze the horizontal displacement and deformation characteristics of the retaining wall during the excavation of an irregularly shaped deep excavation. The results indicate that the pile-internal-support retaining structure performs effectively in irregular deep excavations in Yucheng, exhibiting strong deformation control capabilities. When the pile foundation length was less than 15 m, a reduction in pile length significantly increased the horizontal displacement of the pit support piles, and the reduction of pile length from 22 to 10 m resulted in a 55% increase in maximum displacement. When the distance between the pile foundation and the edge of the excavation increases from 2 to 10 m, the peak horizontal displacement of the retaining piles decreases from 10.76 to 7.23 mm. For every 2 m increase in distance, the average horizontal displacement of the pile body decreases by 0.5 mm, the bending moment decreases by 26%, and surface settlement decreases by 46%. As the pile load increased from 2000 to 7000 kN, the maximum displacement of the retaining structure rose from 9.79 to 10.78 mm. In addition, compared to steel bracing, the concrete internal bracing system significantly enhances deformation control capability. Under full concrete bracing conditions, the minimum horizontal displacement of the retaining structure is 9.20 mm, which is a 23.6% reduction compared to the 12.04 mm under full steel bracing conditions. Furthermore, while increasing the stiffness of the support system to the baseline value improves displacement control, any further increases in stiffness yield limited additional benefits (with a change rate < 12.4%). The study findings can provide a valuable reference for the design of complex, irregularly shaped, deep excavation retaining structures near existing building pile foundations.